Birds and beasts of ancient Latin America - Benson, Elizabeth P. (University Press of Florida, 1997)
"Categorization of animals by domesticated, hunted, anomalous, birds, amphibians and reptiles, fish, crustaceans, and mollusks reveals common themes among depictions from Mexico, Belize, Guatemala, Costa Rica, Panama, Colombia, Ecuador, and Peru"--Handbook of Latin American Studies, v. 57.